Degradation pattern of photosystem II reaction center protein D1 in intact leaves. The major photoinhibition-induced cleavage site in D1 polypeptide is located amino terminally of the DE loop. - Kettunen, R (1996)
Photoinhibition-induced degradation of the D1 protein of the photosystem II reaction center was studied in intact pumpkin (Cucurbita pepo L.) leaves. Photoinhibition was observed to cause the cleavage of the D1 protein at two distinct sites. The main cleavage generated an 18-kD N-terminal and a 20-kD C-terminal degradation fragment of the D1 protein. this cleavage site was mapped to be located clearly N terminally of the DE loop. The other, less-frequent cleavage occurred at the DE loop and produced the well-documented 23-kD, N-terminal D1 degradation product. Furthermore, the 23-kD, N-terminal D1 fragment appears to be phosphorylated and can be detected only under severe photoinhibition in vivo. Comparison of the D1 degradation pattern after in vivo photoinhibition to that after in vitro acceptor-side and donor-side photoinhibition, performed with isolated photosystem II core particles, gives indirect evidence in support of donor-side photoinhibition in intact leaves.